The use of kinesiology tape on Temerloh FA Football team: A study of flexibility and strength / Muhammad Fahmi Zulkifly - Zulkifly, Muhammad Fahmi (Faculty of Sport Science and Recreation, 2017)
The purpose of this study was to investigate the flexibility and strength on Temerloh FA football team between before and after applying kinesiology tape within three weeks intervention. A total subject that has be taken was thirty players (N=30) were selected by purposive sampling. The method of this study is using the experimental group with the same group performing a same test but in different condition. During pre-test all of the subject performing test without applying kinesiology tape while during post-test the subject has applying kinesiology tape with three weeks intervention before. Based on the sample pair t-test result, there a significant difference between before and after applying kinesiology tape which is the p-value of strength (vertical jump) (0.002) and flexibility (sit and reach) (0.001). The p-value is less than 0.05. As the conclusion, kinesiology tape helps to enhance performance in strength and flexibility if the kinesiology tape application applied with the correct ways.